The Moderation Effects of Family Structure and Low Self-Control - McKee, Jesse R. (American journal of criminal justice, 2012)
Gottfredson and Hirschi’s ( 1990 ) theory of low self-control (LSC) asserts the etiology of LSC lies in the ability of parents to correctly control their children. These parental behaviors are crucial to understanding how LSC may or may not be transmitted from parents to children. Little research has explored the potential moderating effects of family structure regarding parenting, LSC, and delinquency. Multi-group structural equation modeling is used with data from the National Evaluation of the Teens, Crime, and the Community/Community Works (TCC/CW) program ( n = 1,409) to assess these relationships. Results show LSC mediates the relationship between family structure and delinquency. Additionally, the relationships between parenting, LSC, and delinquency are invariant for children from intact or broken homes. It is suggested that future research explore the origins of parental efficacy and LSC beyond family structure while considering self-control as a multidimensional concept. Policy recommendations are also discussed.